PEMANFAATAN KAMUS SEBAGAI SARANA PENINGKATAN LITERASI MEMBACA PADA ANAK USIA DINI - Heru Pratikno (Universitas Muhammadiyah Metro, 2023)
Reading activity is something that is now rarely done by today's children. One reason is that many of them do not know the meaning of the words or terms contained in the book. That way, they do not fully understand the substance of the book they are reading so they become lazy to read other textbooks. Therefore, it is necessary to introduce a dictionary for them to make it easier for them to find out difficult things from the books they read. In addition, this study also aims to find out other benefits of introducing dictionaries to young children. The research method used in this study is a qualitative approach. The research results obtained from this study indicate that introducing dictionaries to children from an early age can increase their literacy interest in textbooks. In addition, children will become fond of reading books, both science books and children's literature.